2017
DOI: 10.4236/oje.2017.71002
|View full text |Cite
|
Sign up to set email alerts
|

Annual Fluctuations and Displacements of Inter Tropical Convergence Zone (ITCZ) within the Range of Atlantic Ocean-India

Abstract: Inter Tropical Convergence Zone (ITCZ) is one of the major systems in making the general circulation of atmosphere. Many climatologists believe that the starting point of the general circulation of atmosphere is from this system. It seems that the annual displacement of this system is coordinated with the sun. In this study we have tried to investigate the annual and seasonal displacement of this system within the range of Middle East, especially within the range of longitude of Iran in a long period of time (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 18 publications
(16 reference statements)
1
2
0
Order By: Relevance
“…1b). This observation is further supported by analyses of the low-level wind trajectory cluster composites of February in those years when the southern boundary of the ITCZ was anomalously north or south (Lashkari et al, 2017;Freitas et al, 2017) of its long-term mean February position ( Fig. S1a, b in the Supplement).…”
Section: Climatologysupporting
confidence: 59%
“…1b). This observation is further supported by analyses of the low-level wind trajectory cluster composites of February in those years when the southern boundary of the ITCZ was anomalously north or south (Lashkari et al, 2017;Freitas et al, 2017) of its long-term mean February position ( Fig. S1a, b in the Supplement).…”
Section: Climatologysupporting
confidence: 59%
“…The corresponding statistical and significance test results are generated in Table 1. A hemispheric asymmetry can be observed through the results: the means of all the parameters are higher in the NH than SH for ocean (3.58 mm/day, 13.45%, 23.87 mm/day in the NH vs. 2.50 mm/day, 11.17%, 19.18 mm/day in the SH for MR, RF and CR, respectively) due to the NH-deflection of ITCZ [38]; and inverse phenomena can be observed for land (2.10 mm/day, 5.61%, 34.24 mm/day in the NH vs. 3.29 mm/day, 8.31%, 37.11 mm/day in the SH for MR, RF and CR, respectively) because the maritime continent and Amazon rainforest are mainly distributed in the SH [39,40]. The mean values of MR calculated in this study are comparable to those of GPCP V2.3 (2.95 mm/day for tropical, 3.0 mm/day for ocean, and 2.81 mm/day for land) [37].…”
Section: Global Meansmentioning
confidence: 86%
“…However, the divergence of air ow in the low-pressure west of the Persian Gulf caused decreased air ow on the surface and vorticity advection of −2.5 × 10 −5 S −1 (m/s) on Iran's southern half. However, Lashkari showed that in a lowpressure ow, depending on the density of air and the input ow of air to its east, convergence occurs, and in its western part, divergence occurs due to the high speed of air ow [42][43][44][45]. Such a situation is clearly shown in Figure 3(a).…”
Section: E First Pattern: Low Pressure Of Persian Gulf Dual-mentioning
confidence: 99%